Overview of fluid and macronutrient intake, knowledge and attitudes and eating behavior among private university medical students in Jakarta - Luciana Budiati Sutanto; Gracia JMT Winaktu; Helena Fabiani; Leilani Lestarina (Indonesian Nutrition Association, 2024)
Background: Adequate intake of micronutrients and fluids are important for study performance of students Objective: To obtain an overview of macronutrient and fluid intake, also knowledge, attitudes, and healthy eating behavior of medical students from Krida Wacana Christian University (UKRIDA) Methods: This is a cross sectional study conducted in October 2021 based on consecutive sampling. Height and weight was self-recorded, while the food and fluid intake was assessed via a phone interview using a 3-day diary. There were 97 students who met the inclusion and exclusion study’s criteria who participated in macronutrient and fluid intake data, and 90 of them for the knowledge, attitudes, and healthy eating behavior data. Results: As much as 10.3% of the study participants were underweight, 41.2% normal, and 48.5% overweight-obese. For macronutrient intake, compared to the RDA, 95.9% of subjects had inadequate energy intake, 100% had inadequate carbohydrates intake, 85.6% for fat intake and 55.7% for protein intake. For fluid intake, 76.3% of respondents had less, 18.6% had adequate, 5.1% had more than RDA. For the nutrition knowledge, 85.6% of respondents had good, 12.2% had sufficient, and 2.2% had inadequate nutrition knowledge. For the respondents’ eating habits, 91.1% of respondents reported good, 7.8% adequate, and 1% non-healthy Conclusion: Most of the subject had inadequate intake of energy, macronutrients, and fluids. Knowledge and attitudes towards healthy eating are mostly good, while healthy eating behavior can be further improved.